Types of Socialization and Their Importance in Understanding the Phenomena of Socialization - Crisogen, Disca Tiberiu (European Journal of Social Science Education and Research, 2016)
Depending on various criteria, the specialized literature defined several types of socialization. After socialization factors and the age at which the process are studied, we have primary socialization and secondary socialization (and continues), according to the assessment of society there are positive or negative socialization, and as awareness of how socialization process is distinguished there is formal or informal socialisation, depending on the objective pursued by already created effects, we have anticipatory or adaptive socialization , depending on the intervention of legitimate power we can talk about associative or institutional socialization after as contents and the results expressed in statuses and roles, gender socialization may be , professional, marital, according to methods of making can speak about planned, spontaneous, law enforcement, participatory socializing depending on the purpose we have societal, national, political, ideological-partisan socialization etc.. These types are not individualized in an environment amorphous, but they intermingle, they complement and, by correlation, manage to describe the complex phenomenon of socialization. The contribution of those who have defined numerous types of socialization should not be approached holistically, nor in opposition with each other, but as a complement to the comprehensive and specialized understanding of socialization. In this context, we propose a new criterion for classification, namely the extent of socialization, which assumes a total socialization of one partial socialization and a zero socialization, void. In regards the overall socialization, this is an ideal and not a reality. However, at least in theory, we could use this terminology as, for example, education sciences use the term " ideal educational " or how physics used the notion of "ideal environment". The concept of "zero socialization" could be the social equivalent of the expression used by Aristotel in his "De anima": a kind of "blank slate" for the socialization.